A internet como ferramenta metodológica para o ensino de matemática no segundo ano do ensino médio - BATISTA, Neilson Martins (2022)
The work results from a qualitative, descriptive research whose main objective was to understand how the Internet can be used as a methodological tool in the teaching of mathematics. For that, a field study was carried out at the State School of Elementary and Middle School Dr. Maroja Neto, in the city of São Domingos do Capim, Pará, developed in two stages: interviews with teachers and students and intervention process using video The choice of topic was due to the difficulties presented by students regarding the learning of mathematical contents and their predisposition to use the internet and social networks, configuring possible tools for the methodological assistance of these students. It was possible to verify that the internet can help as a tool for teaching mathematics, however, the planning process should take into account both the educational objectives, the methodological choices and the evaluation process associating them with the use of the tool, to that it does not just serve as a distraction.